Frances Ridley Havergal's Theology of Nature. (4th January 2016) - Atherstone, Andrew
Abstract : Historians of the nineteenth-century Keswick holiness movement have long observed, though seldom analysed, its theological appropriation of the natural world. With annual conventions held from 1875 in the Lake District, home territory of Wordsworth and Southey, the movement's love of nature was one of its most obvious 'Romantic afFinities' and marked it out from other streams of contemporary Evangelicalism, as David Bebbington has recendy shown. Yet much of the early theological inspiration behind the Keswick Convention was drawn not from the Lake Poets, but from the devotional writings of Victorian England's best-known evangelical poet, Frances Ridley Havergal. The Keswick emphases upon absolute surrender to God and 'entire consecration' in his service, with a deep christocentric piety and a passion for spiritual transformation, pervade her teaching. Although Havergal's brief career lasted only two decades, being cut short by her untimely death in June 1879 at the age of 42, her output was prodigious. Alongside indefatigable letter-writing and the production of numerous evangelistic booklets, she published several collections of poetry and hymnody in a short space of time, notably The Ministry of Song (1869), Under the Surface (1874), Loyal Responses (1878) and, posthumously, Under His Shadow (1879). Her popular hymns, such as 'Take My Life' and 'Like a River Glorious', became synonymous with Keswick spirituality.